Knowledge and Practice of TB Notification among the Private Health Care Providers in Eastern India - R Akshaya; Binod Kumar Behera; Binod Kumar Patro; Arvind Kumar Singh (Indian Journal of Community Medicine)
Tuberculosis (TB) has been a notifiable disease since 2012. The study aimed to assess the knowledge and practice of private health care providers (PHCPs) regarding TB notification and to identify the physician-level and health system-level factors determining knowledge and practice of TB notification. A cross-sectional study was done in the field practice area of AIIMS Bhubaneswar. The study was conducted from February 2020 to May 2021 in Odisha. PHCPs from all systems of medicine were included in the study. The sample size was calculated to be 138. A self-administered semistructured questionnaire was used to collect the data. Multivariable logistic regression was done to identify the association between the independent and dependent variables. A total of 89 PHCPs were recruited into the study. Among them, 57 (64%) of the PHCPs were aware of TB notification, whereas 24 (42%) had ever notified a case of TB. All PHCPs who had ever diagnosed or treated a TB case were aware of TB notification. The factors associated with TB notification were the clinical setting of practice, diagnosed more than one TB case in the past 1 year, and those who worked in the government setting in the past 2 years. The knowledge and practice of TB notification were low among PHCPs. More frequent and mandatory sensitization training should be conducted for all PHCPs to increase awareness about TB notification.